Characterization of white grub (Melolonthidae; Coleoptera) in salak plantation based on morphology and protein banding pattern - KRISNANDARI TITIK MARYATI; SUGIYARTO SUGIYARTO (Nusantara Bioscience, 2009)
Abstract. Maryati KT, Sugiyarto. 2010. Characterization of white grub (Melolonthidae; Coleoptera) in salak plantation based on morphology and protein banding pattern. Nusantara Bioscience 1: 72-77. This research aims to find out the white grub (Melolonthidae; Coleoptera) variability based on the morphological characteristic and protein banding pattern found in "salak pondoh" farm in Regencies of Sleman, Yogyakarta and Magelang, Central Java. Each area has five sampling points. Morphological analysis on white grub was conducted using descriptive method and analysis on protein banding pattern was conducted using qualitative analysis based on the presence or absence of band pattern on the gel, and qualitatively based on the relative mobility value (Rf) of protein. The result indicated that the white grub in Sleman and Magelang, based on morphology characteristic is only one species, namely Holothricia sp. Based on the protein banding pattern, the white grub sample has differences in protein band number and molecular protein weight.